2008
DOI: 10.1007/s00418-008-0407-x
|View full text |Cite
|
Sign up to set email alerts
|

Localized matrix metalloproteinase (MMP)-2 and MMP-9 activity in the rat ventral prostate during the first week of postnatal development

Abstract: The initial events in prostatic morphogenesis involve cell proliferation, epithelial canalization and outgrowth toward the stroma. We have hypothesized that stromal rearrangement takes place at the sites of epithelial growth and branching and that this rearrangement involves the action of gelatinases matrix metalloproteinase (MMP)-2 and MMP-9. Thus, the purpose of the present study was to characterize structural aspects of epithelial growth during the first week of postnatal development of the rat ventral pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 53 publications
5
33
0
2
Order By: Relevance
“…Using immunohistochemistry, MMP-2 was found in the mouse VP on day 6, in both stroma and epithelium, being more concentrated in the epithelial distal regions (Fig. 1A), suggesting a role for this enzyme during epithelial branching and elongation, findings that are in agreement with our earlier in vitro and ex vivo studies in the rat (Bruni-Cardoso et al, 2008. Tissue organization was determined by stereology.…”
Section: Mmp-2 Promotes Branching and Epithelial Proliferation In Vp supporting
confidence: 87%
See 3 more Smart Citations
“…Using immunohistochemistry, MMP-2 was found in the mouse VP on day 6, in both stroma and epithelium, being more concentrated in the epithelial distal regions (Fig. 1A), suggesting a role for this enzyme during epithelial branching and elongation, findings that are in agreement with our earlier in vitro and ex vivo studies in the rat (Bruni-Cardoso et al, 2008. Tissue organization was determined by stereology.…”
Section: Mmp-2 Promotes Branching and Epithelial Proliferation In Vp supporting
confidence: 87%
“…Using an in vitro/ex vivo organogenesis model, we previously reported that the activities of MMP-2 and -9 are higher and localized in the distal ductal region and at the epithelial/ stromal interface of rat VP during the first postnatal week (Bruni-Cardoso et al, 2008). Subsequently, we showed that MMP-2 modulates the morphogenesis of the rat ventral prostate in vitro by influencing the epithelial cell proliferation rate, branching, and the canalization of the epithelium, and the remodeling of collagen fibers (Bruni-Cardoso et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estes, por sua vez, irão estimular atividades específicas nas células prostáticas, como a proliferação das células epiteliais (KGF) e estromais (FGF). Durante o desenvolvimento embrionário, por exemplo, as células mesenquimais do complexo prostático em desenvolvimento são as primeiras a expressar AR e, então, sob o estímulo androgênico, liberam fatores como o FGF-10 que agem sobre as células epiteliais induzindo a formação dos ductos prostáticos e seu padrão de ramificação característico (14,15,17,18). Por sua vez, a ação direta dos andrógenos se aplica principalmente para a regulação da atividade secretora das células epiteliais (19).…”
unclassified